Effect of process factors on properties of high dispersion spherical α-Al2O3 particles prepared by hydrothermal method. Issue 17 (1st December 2019) - Xiang, Hairu; Wang, Zhiyuan; Yin, Qiao; Wang, Lei; Zhang, Liwei; Wang, Hailong; Xu, Hongliang; Zhang, Rui; Lu, Hongxia
Abstract: Spherical α-Al2 O3 powders were synthesized from a mixed solution consisting of Al2 (SO4 )3 ·18H2 O, Al(NO3 )3 ·9H2 O and CH4 N2 O by hydrothermal method with muffle calcination and microwave calcination. Effects of raw material ratio, reaction temperature, and filling factor on properties of products were investigated. Properties of thermal behavior, functional groups, phase composition, microstructure and specific surface of precursors and products were characterized by DSC-TG, FT-IR, XRD, SEM and BET, respectively. Results show that SO4 2− plays an important role in the sphere formation of precursors and particle size can be changed by adding different proportion of NO3 − . Precursors are amorphous spherical hydrated alumina containing SO4 2−, and the conversion of crystalline phase is from amorphous to γ-phase and then to α-phase at 1100 °C. Spherical morphology can be retained after crystallization to α-Al2 O3 . Compared with muffle furnace, Microwave calcination can increase calcining rate by three times and reduce insulation time by three quarters. When hydrothermal reaction temperature is 120 °C, the particles can be precipitated with good sphericity and narrow grain size distribution. If hydrothermal reaction temperature is too high or too low, spherical morphology can't be obtained. Size of the particles can be regulated by the different raw material ratio and filling factor from 800 nm to 3 μm, and specific surface area is in the range of 8 m 2 /g~15 m 2 /g.